Analisis Isim Ma’rifat dalam Al-Qur’an Surat Ash-Shaff - M. Zakki Mubarok; Nurkholis; Muhammad Irham (Program Studi Pendidikan Bahasa Arab, 2021)
The background of this research is the importance of understanding the science of nahwu which is very influential on the meaning of words in Arabic and the number of students who still do not understand Tarkib Ma'rifat in nahwu. This thesis discusses Isim Ma'rifat and his learning methods in the Al-Qur'an letter Ash-Shaff. The formulation of the problem in this study is how many Isim Ma'rifat are contained in the Al-Qur'an letter Ash-Shaff. In addition, this study aims to determine and describe the analysis of Isim Ma'rifat through the nahwu science approach and to find out the number of Isim Ma'rifat contained in the Al-Qur'an letter Ash-Shaff. This research is library research, namely research that takes research materials from several book references or books that are in accordance with the research theme by taking data from the Al-Qur'an letter Ash-Shaff using descriptive analysis. The data collection is by means of qualitative documentation of primary and secondary data sources. Isim Ma'rifat consists of seven types, including Isim Dhamir, Isim 'Alam, Isim Isyarah, Isim Maushul, Isim Mu'arraf bi Alif Lam, Isim Mudhaf ila Ma'rifah, and Isim Munada Maqshud Ta'yinuhu. The results of research from the Al-Qur'an letter Ash-Shaff there are 138 Isim Ma'rifat. Through this research, it is hoped that it can provide benefits and can be used as literature in Literature Review research.